Restraint A New Foundation For U.S. Grand Strategy - Mr. Khusrow Akkas Abbasi (CISS Insight Journal, 2015)
The main thesis of the book Restraint A New Foundation For U.S. Grand Strategy is that the US pursuit of its current grand strategy is unable to achieve its objectives in the contemporary international political environment. Since the end of Cold War it has pursued a grand strategy which the author calls ‘liberal hegemony’. The author believes that the US’ grand strategy is hard to practice, counterproductive and needs more resources. The author comes up with a number of reasons against the prevailing grand strategy of liberal hegemony and offers an alternate – a grand strategy of Restraint.The author, Barry R. Posen, is Ford International Professor of Political Science at MIT and Director of the MIT Security Studies Program. He has written two books earlier Inadvertent Escalation: Conventional War and Nuclear Risks and The Sources of Military Doctrine. He has been a Council on Foreign Relations International Affairs Fellow; Rockefeller Foundation International Affairs Fellow; Guest Scholar at the Center for Strategic and International Studies; Woodrow Wilson Center Fellow; Smithsonian Institution; Transatlantic Fellow of the German Marshall Fund of the United States, and most recently Visiting Fellow at the John Sloan Dickey Center at Dartmouth College.